Recent insights into the transformative role of Graphene‐based/TiO2 electron transport layers for perovskite solar cells - T. Sewela; R. O. Ocaya; T. D. Malevu (Energy Science & Engineering)
Abstract Perovskite solar cells (PSCs) hold great promise for cost‐effective and high‐efficiency solar energy conversion. However, in practice, they face practical limitations due to suboptimal electron transport, inadequate hole‐suppression, photocatalytic instability, and susceptibility to other environmental factors. Many transition metal oxides such as ZnO and TiO2 have important excitonic properties that make them good electron transport layer (ETL) materials in PSCs. However, many of the PS limitations arise from inherent issues with these oxides. The high interest in TiO2 is due to its low toxicity, chemical stability, and the potential to enhance its excitonic performance through doping with many materials. The main limitations of TiO2 are its poor visible‐light response by virtue of its wide bandgap of ~3.2 eV, and its high electron‐hole (e‐h) recombination rates, which are directly responsible for its low current densities. Transition metal oxide enhancements occur using either internal doping or surface sensitization. Of the added materials, graphene has exceptional electrical conductivity, high electron mobility, large surface area, and excellent mechanical properties, making it a near‐ideal candidate to improve the performance of TiO2. This review examines the important advances in graphene‐TiO2 (g‐TiO2) composites for ETL application. By forming a composite with TiO2, graphene can significantly enhance electron transport, reduce recombination losses, and improve the overall stability of PSCs. We present the detailed rationale for and analysis of g‐TiO2 for improved electron transport efficiency, enhanced stability, and boosted overall PSC performance with the objective of providing an authoritative resource for the field.